Confirmation of Allium ruhmerianum Asch. ex E.A.Durand et Barratte as a member of the sect. Molium - Friesen, Nikolai; Abdulkarim, Abdulnaser (Phytotaxa, 2025)
Allium ruhmerianum Ascherson ex Durand et Barratte, an endemic Allium species from Cyrenaica, was examined using anatomical, cytological, and molecular methods to determine its relationship and position within the genus Allium taxonomy. The previously published chromosome number 2n=33 was not confirmed; we counted 2n=14 in all three accessions examined. In conjunction with cytological and anatomical results, the molecular data placed A. ruhmerianum in the Molium section, close to A. neapolitanum and A. palaestinum. These results render the A. section Rynchocarpum Brullo superfluous.